SISTEM INFORMASI PELAYANAN KESEHATAN BERBASIS WEB PADA KLINIK GOCARE - Iswanto Sulila; Agus Lahinta; Mohamad Syafri Tuloli (Gorontalo State University, 2021)
ISWANTO SULILA. The GOCARE Gorontalo clinic health service has several obstacles that cause the service to be not optimal such as the ordering process, which still uses telephone and WhatsApp that resulted in the lack of expected information Another obstacle is frequemt delays in service due to the absence of service scheduling that make customers unable to be served optunally This study aimed to design and create a Web-based health service information system at the GOCARE clinic. The system development method used in this research is the Prototype method using the PHP programming language and MySQL database. The results and this study indicated that the health service information system at the GOCARE clinic could facilitate services. The system can make it easter for related parties to carry out the service process according to the procedure, the system can also order services because the schedule has been set, the system is also able to record patient medical records that it makes # easier to provide services. This system is used to facilitate existing health service users in the GOCARE Gorontalo Clinic environment. Keywords: Health Service, Web, Prototype